C20-C21-C23 tricyclic terpanes abundance patterns: Origin and application to depositional environment identification - Wang, Aiguo; Li, Chunyu; Li, Long; Pu, Renhai; Yang, Zeguang; Zhu, Nan; Guo, Kai (Frontiers in Earth Science, 2023)
Reconstruction of paleo-depositional environments in a sedimentary basin is often obstructed by the absence of typical environmental indicators in sedimentary rocks. Here, we propose a biomarker method using C20-C21-C23 tricyclic terpanes (TTs) as a tracer, which is simple in analysis but robust to provide reliable and detailed environmental information. Based on the analysis of 271 C20-C21-C23TT data from 32 basins in 18 countries, we observed a relationship between C20-C21-C23TT abundance patterns and depositional environments. This relationship was attributed to the control of depositional environments on the input proportions of plankton and terrigenous plants, which act as two end-member precursors for the TTs in a depositional system. The various mixing proportions between these two end-members result in different C20-C21-C23TT abundance patterns associated with different depositional environments, e.g., C20>C21>C23TT in river-lake transitional, C20C23TT in freshwater lacustrine and C20>C21